PENGARUH VOLUME FRAKSI SERAT TERHADAP KEKUATAN TARIK KOMPOSIT BERPENGUAT SERAT IJUK Ø 2 MM - Agussetiawan, Ledie; Yulianto, Yulianto; Arianto, Arianto (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
This research was conducted to obtain data on the effect of the volume fraction of palm fiber on the tensile strength, modulus of elasticity and impact strength of composites using a 157 Ortho-phthalic Unsaturated Polyester matrix with the hand lay-up method. The object of this research is a composite of palm fiber 2 mm with a variation of fiber volume fraction 15%, 25%, 30%. The highest tensile stress of fiber-reinforced composite 2 mm was found in the volume fraction of 25% with a value of 30.23 MPa. Meanwhile, the highest value of modulus of elasticity is in the volume fraction of 25%, which is 9063.33 MPa. And for the highest impact strength, fiber-reinforced composite 2 mm is found in the volume fraction of 30% with a value of 49.3 Kj/mm². Meanwhile, the lowest tensile strength is found in the volume fraction of 15% with a value of 15.9 MPa. And the lowest elastic modulus value is found in the 15% volume fraction with a value of 7046.66 MPa. And for the lowest impact strength value is in the 25% fraction with a value of 29.73 Kj/mm².